Effect of alkyl side-chain length on the photophysical, morphology and photoresponse properties of poly(3-alkylthiophene). (5th November 2015) - Xu, Wei-Long; Yang, Xiao-Yu; Zheng, Fei; Jin, Han-Dong; Hao, Xiao-Tao
Abstract: The effect of alkyl side-chain length on the photophysical, morphology and photoresponse properties of poly (3-alkylthiophene) (P3AT) has been investigated. Butyl, hexyl, octyl, decyl, and dodecyl side chains have been studied. In solution state, the average lifetime of poly (3-octylthiophene) (P3OT) is the shortest among P3AT solution owing to the strong intrachain interaction. The fluorescence lifetime of P3AT solution increases with the side-chain length increasing. A similar trend occurs in the P3AT films. This phenomenon illustrates conformation 'memory' property evolving from solution state to solid film. The four lifetimes represent different photophysical processes and have been systematically analyzed. The photodetector based on P3DDT is a suitable candidate for practical application owing to the fast, reversible photoresponse and photostability. The high performance of P3DDT-based photodetector is correlated to the optimized morphology and strong interchain interaction which promotes the exciton delocalization.